التوازن الما لي وأثره على نظام مؤسسة إقتصادية - لخضار, أمينة (My University, 2020)
We aim, through this study, to know more about the importance of financial balance in determining the financial position of the institution by identifying the most important financial analysis tools and its role, in order to reach a correct diagnosis of the status of the institution and the nature of the relationship between the analysis and the financial balance by studying the case of Mostaganem port (EPM). A number of results were reached that the financial analysis is one of the most important financial positions of the economic institution in order to reach the correct diagnosis and achieve the financial balance of the institution, which is the goal of any financial manager to strengthen the financial position of the institution by achieving profits and reaching goals that reflect the strength and efficiency of the institution, which contributes to improving Its financial performance.
دراسة حالة ميناء مستغانم EPM
Keywords: التحليل المالي ،التوازن المالي ،الأداء المالي